Pseudoprogression during induction treatment with nivolumab plus ipilimumab combined with chemotherapy for metastatic lung adenocarcinoma: A case report - Yusuke Kunimatsu; Yukari Kano; Rei Tsutsumi; Izumi Sato; Mai Tanimura; Keiko Tanimura; Takayuki Takeda (Respirology Case Reports, 2023)
Abstract The incidence rate of pseudoprogression during immune checkpoint inhibitor monotherapy for non‐small cell lung cancer is reportedly 3.6%–6.9%, while pseudoprogression during chemoimmunotherapy is rare. Reports on pseudoprogression during dual immunotherapy combined with chemotherapy are lacking. Herein, a 55‐year‐old male with invasive mucinous adenocarcinoma (cT2aN2M1c [OTH, PUL], stage IVB, and programmed death‐ligand 1 expression <1%), renal dysfunction, and disseminated intravascular coagulation was treated with carboplatin, solvent‐based paclitaxel, nivolumab, and ipilimumab. After treatment initiation, computed tomography (CT) on day 14 showed disease progression. The patient was diagnosed with pseudoprogression because of a lack of symptoms, improved platelet count, and decreased fibrin/fibrinogen degradation product levels. CT on day 36 showed a reduction in the primary lesion size, multiple lung metastases, and mesenteric metastases. Therefore, pseudoprogression should be considered during dual immunotherapy with chemotherapy.